IMPLEMENTASI SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN UNTUK MENJAMIN PELUNASAN KREDIT KEPEMILIKAN RUMAH BERDASARKAN PASAL 1 PERATURAN MENTERI AGRARIA NOMOR 4 TAHUN 1996 - Noviria Hasty Ananda (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstrackPower Mortgage provided for in Article 15 of Law No. 4 1996 determining the time limit of 1 (one) month for the right to land that is already registered and 3 (three) months for the right to land that has not been registered, but these provisions do not apply to the types of credit as are regulated by the State minister of Agrarian Affairs / head of BPN No. 4 of 1996, which specifies that for certain types of credit Letters of Mortgage (SKMHT) is valid until the expiration of the credit agreement. The discussion in this paper include the principle of legal agreements and additional agreements on housing loans in terms of rules of law regarding SKMHT in agreement Housing loans are closely related to the setting of time limits SKMHT as the basic philosophy of setting a time limit SKMHT and the latter's result law for creditors if SKMHT not followed up with the creation of REITs.Keywords : mortgage, Power of  Attorney Imposing  Mortgage